2018
DOI: 10.5194/acp-2018-725
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mineralogy and mixing state of North African mineral dust by on-line single-particle mass spectrometry

Abstract: Abstract. The mineralogy and mixing state of dust particles originating from the African continent influences climate and marine ecosystems in the North Atlantic due to its effect on radiation, cloud properties and biogeochemical cycling. Single-particle mineralogy and mixing state is particularly important in many processes but is difficult to predict because of large temporal and spatial variability and the lack of in-situ measurements of dust properties during emission, transport and deposition. This lack o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…However, their relative amounts are significantly lower than those of feldspars and quartz. 67 It should be also noted that molten clays can transform into feldspars as they mostly consist of phyllosilicates 60 . Our model dust minerals were thus assumed to contain only feldspars and quartz.…”
Section: Mineral Dust Model Selection and Validationmentioning
confidence: 99%
See 3 more Smart Citations
“…However, their relative amounts are significantly lower than those of feldspars and quartz. 67 It should be also noted that molten clays can transform into feldspars as they mostly consist of phyllosilicates 60 . Our model dust minerals were thus assumed to contain only feldspars and quartz.…”
Section: Mineral Dust Model Selection and Validationmentioning
confidence: 99%
“…67 It should be also noted that molten clays can transform into feldspars as they mostly consist of phyllosilicates. 60 Our model dust minerals were thus assumed to contain only feldspars and quartz. Since…”
Section: Mineral Dust Model Selection and Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…A combination of peak area and peak shift ratio, based on subtle changes in ion arrival times in the mass spectrometer, was introduced by Marsden et al (2018a) for the differentiation of mineral phases in silicates. Ternary sub-composition systems, such as (Al+Si) + -K + -Na + and Cl --(CN+CNO) --SO 4 -,were used to identify mineralogy and internal mixing state of ambient particles (Marsden et al, 2018b). In our previous study (Shen et al, 2018), laboratory-based reference spectra were suggested to be a useful tool for particle identification.…”
mentioning
confidence: 99%